Ciclosporin compared to prednisolone therapy for patients with pyoderma gangrenosum: cost-effectiveness analysis of the STOP GAP trial - Mason, J.M.; Thomas, K.S.; Ormerod, A.D.; Craig, F.E.; Mitchell, E.; Norrie, J.; Williams, H.C. (Wiley, 2017)
Background